Persistent current account imbalances: Are they good or bad for regional and global growth? - John Beirne; Nuobu Renzhi; Ulrich Volz (Asian Development Bank Institute (ADBI), 2020)
This paper examines the regional and global growth effects of current account imbalances in Japan, Germany, and the People's Republic of China (PRC) - the three largest persistent surplus countries - and the United States and United Kingdom, the two largest persistent deficit countries. Controlling for a set of macroeconomic determinants, we use a structural vector autoregression (SVAR) framework to show that positive shocks to current account balances in the PRC, Germany, and Japan transmit positive regional and global growth effects, particularly in the case of spillovers to regional growth from Japan. As expected, the global growth response is lower in magnitude than the regional growth response. In addition, the extent of the effect is amplified by global value chains, pointing to the significant role played by trade in intermediate goods. For current account deficit countries, the magnitudes of the responses of growth to shocks are much lower on average than in the case of current account surplus countries. We find some marginal positive effects on regional and global growth emanating from a positive shock on the UK current account - i.e., a reduction in the deficit. For the US, a positive shock to its persistent current account deficit marginally drags on global growth, possibly reflecting declining import demand and wealth effects linked to the US dollar's status as the global reserve currency. Our findings have important policy implications at the global level, particularly in light of the re-emergence of discussions on global imbalances in recent years.
Keywords: F32; F41; F62; 330; current account imbalances; macroeconomic imbalances; economic growth